2001
DOI: 10.1007/s004310000579
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure monitoring in children with unilateral multicystic dysplastic kidney

Abstract: Arterial hypertension in children with multicystic dysplastic kidney is seen more often if based on ambulatory blood pressure monitoring than on casual blood pressure recordings. The main risk factor for developing hypertension is contralateral kidney damage. Ambulatory blood pressure monitoring should be performed in children with multicystic dysplastic kidney, especially in those with contralateral kidney abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 22 publications
0
23
1
Order By: Relevance
“…Malignant transformation [1,2,[16][17][18] and hypertension [1,2,[19][20][21][22] associated with MCDK have been reported in the literature. Routine nephrectomy was performed in many centers to prevent those complications before 1990.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant transformation [1,2,[16][17][18] and hypertension [1,2,[19][20][21][22] associated with MCDK have been reported in the literature. Routine nephrectomy was performed in many centers to prevent those complications before 1990.…”
Section: Introductionmentioning
confidence: 99%
“…Mei-Zahav et al [11] have reported that the systolic, but not the diastolic, ambulatory BP is higher in children with URA in comparison with healthy children. However, we have shown in our previous study done in children with a solitary kidney due to a contralateral multicystic dysplastic kidney [14] that the main risk factor for hypertension in these patients seems to be a structural damage of the solitary kidney, such as renal scarring, reflux, or obstructive uropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the general population there is no clinically significant increased risk of hypertension. The incidence of hypertension has been reported to be 0.5% to 14.4% in the MCDK population (12)(13)(14)(15) . In our study population, the rate of hypertension (16.6%) was found to be higher than the expected rates (Table 1).…”
Section: Discussionmentioning
confidence: 99%